2020
DOI: 10.3390/languages5040046
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehension of Tense–Aspect Morphology by Spanish Heritage Speakers in the United Kingdom

Abstract: Whilst heritage Spanish has been widely examined in the USA, less is known about the acquisition of Spanish in other English-dominant contexts such as the UK, and studies rarely assess the baseline grammar that heritage speakers are exposed to directly. In this study, we implemented a semantic interpretation task to 17 bilinguals in the UK to investigate child heritage speakers’ and their parents’ comprehension of the preterite–imperfect aspectual contrast in Spanish, an area of known difficulty. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…These findings align with some previous studies on other areas of the Spanish inflectional system that have found a facilitative effect for age (Corbet and Domínguez 2020;Cuza and Miller 2015;Martinez-Nieto and Restrepo 2022;Montrul and Potowski 2007; see also Flores et al 2017 concerning European Portuguese HSs), which points to protracted HL development of inflectional morphology. These studies differ, however, from some previous work on child Spanish HSs that reports attrition of morphosyntactic structures (Goebel-Mahrle and Shin 2020; Merino 1983), as well as the predictions that Putnam and Sánchez (2013) advance, since it does not appear that bilingual children are restructuring their grammatical repertoire over time.…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with some previous studies on other areas of the Spanish inflectional system that have found a facilitative effect for age (Corbet and Domínguez 2020;Cuza and Miller 2015;Martinez-Nieto and Restrepo 2022;Montrul and Potowski 2007; see also Flores et al 2017 concerning European Portuguese HSs), which points to protracted HL development of inflectional morphology. These studies differ, however, from some previous work on child Spanish HSs that reports attrition of morphosyntactic structures (Goebel-Mahrle and Shin 2020; Merino 1983), as well as the predictions that Putnam and Sánchez (2013) advance, since it does not appear that bilingual children are restructuring their grammatical repertoire over time.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in adult heritage Russian in the US have reported vulnerability or loss of aspectual distinctions, which they mostly attribute to Attrition over the lifespan (e.g., Polinsky, 2008), the Bottleneck Hypothesis (e.g., Mikhaylova, 2018), and the Interface Hypothesis (e.g., Laleko, 2010). Moreover, studies on heritage Spanish in the US found inaccurate production of aspect, avoidance errors, and low accuracy which they attribute to Attrition and/or Incomplete Acquisition of aspect in Spanish (Cuza et al, 2013;Corbet & Dominguez, 2020;Montrul, 2002;Montrul & Perpiñan, 2011;van Buren, 2012) and an overuse of the perfective form which they attribute to cross-linguistic influence from English.…”
Section: Zooming In Minority Languages: Acquisition Of Aspect In Heri...mentioning
confidence: 99%